Challenges in designing an interethnic-content survey among b40 urban multi-ethnic women in Kuala Lumpur - Rokis, Rohaiza; Muhamad Fauzi, Faten Nadhirah; Wan Husain, Wan Rohaida (Universiti Kebangsaan Malaysia, 2021)
The article elaborates researchers’ challenges in designing a structured survey on B40 urban women across three major ethnic groups in a multi-ethnic city of Kuala Lumpur, Malaysia. It is an outcome of a sociological, quantitative research. A major focus of this article is to enrich the knowledge associated with designing a survey questionnaire involving interethnic study – a field that has a direct impact on any diverse-cultural societies. It provides an overview of methodological matters in conducting research on the interethnic theme. Its main objective is to raise understanding about methodological issues and procedures in designing the interethnic content survey. It is found that in designing the research questions and items in interethnic studies, researchers need to comprehend the socio-cultural-historical-political experiences of each ethnic group in Malaysia. This article hopes to provide helpful guidance to future researchers to engage in interethnic study. Understanding the influences of ethnic diversities regarding social relations is pertinent within the Malaysian context.